Formal Modeling of Trust Web Service Composition Using Pi-calculus - Bensheng YUN (Institute of Advanced Engineering and Science, 2013)
To enhance the credibility of Web service composition, Pi-calculus based formal modeling of trust Web service composition is proposed. Trust Web service composition is firstly defined abstractly; then Pi-calculus is used to depict structure and internal interaction of Trust Web service composition, the mapping relation between trust entity and Pi-calculus is provided. Automatic reasoner MWB is adopted to analyze and reason the Trust Web service composition system, which is aimed at finding and correcting the faults before the implementation of trust authentication of Web service composition. It thus meets the users’ demands on trust quality effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3039